IMPROVEMENT OF THEORETICAL BASIS OF INTERNAL CONTROL OF TOURIST INDUSTRY ENTITIES - BARDASH, Serhii; SHAPOVALOVA, Valentina; PASHKOVA, Alla (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The tourism industry of Ukraine is one of the underestimated branches of the national economy. Since 2014, its condition has depended on a number of external factors that had mostly negative consequences (loss of tourist infrastructure and decrease in domestic tourist flows due to the annexation of part of the territory of Ukraine by the Russian Federation in 2014, negative consequences of COVID-2019 after 2020, full-scale military aggression of the Russian Federation in 2024). Currently, the search for financial resources to finance the activities of tourism industry entities is significantly limited. One of the sources of determining internal reserves and optimizing the management of available resources is the establishment of effective internal control systems. The purpose of the article is to determine the main elements of the internal control system (object, subject, control actions) of subjects of the tourism industry. The methodological basis of the research is the dialectical, abstract-logical and bibliographic methods, as well as the methods of induction, deduction, analysis and synthesis, with the help of which the main elements of the system of internal control of the entities of the tourism industry are clarified based on a critical analysis of the established concepts and the results of the latest research. Based on the results of the research, it was established that each subject of the tourism industry should create a system of internal control, the complexity of which will depend on the organizational and legal form, the size of the business, the number of personnel, financial and technical capabilities, as well as the chosen business strategy. It is proven that the integrated object of internal control is the economic activity of the subject of the tourism industry, which consists of resources, processes and results of its activity. Considering the fact that the content of the activity of the vast majority of subjects of the tourism industry is the provision of services that have their own intangible specifics, the composition and content of the processes will differ from the sphere of material production. This feature will also affect resource provision, because the composition of production factors will also have certain differences. All components of the integrated object of internal control must be detailed, because this will allow to specify the purpose and tasks of its implementation for each of the objects, as well as to determine the methodology of its implementation (to determine those methodical methods of control that will allow solving the tasks set before the subject - the executor of the control measure). Determining the subjects of internal control with their division into initiators and executors, as well as control measures, will contribute to the development of internal regulations for conducting internal control and evaluating its effectiveness. Prospects for further research will consist in the specification of internal control systems by types of entities of the tourism industry and the study of their impact on management systems in conditions of uncertainty.